Synthesis and characterization of nylon-610 phase change materials with varied reduced graphene oxide filler ratios - Fadhl Al-Mahmodi Akram; Saii Patmashini; Munusamy Yamuna; Muniyadi Mathialagan; Siong Leong Sim (E3S Web of Conferences)
This study delves into the synthesis and comprehensive characterization of Nylon-610 (PA610) phase change materials (PCMs), augmented with varied ratios of reduced graphene oxide (rGO) fillers, to assess their compatibility and integration within the polymer matrix. Utilizing condensation polymerization, PA610 was synthesized and incorporated with rGO fillers across a spectrum from 0 to 2.0 wt%, aiming to explore the interaction between the polymer and the fillers. The characterization of the synthesized composites was meticulously conducted through Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD) analyses. The FTIR results provided insights into the chemical bonding and interactions between PA610 and rGO, indicating successful integration of the fillers into the polymer matrix. Concurrently, XRD analysis revealed changes in the crystalline structure of PA610 with the introduction of rGO, suggesting an alteration in the material's microstructure due to filler addition. This research aims to illuminate the fundamental aspects of filler compatibility within polymer based PCMs, offering a novel perspective on the design and development of advanced materials for energy storage applications.